SELECTION OF THERAPEUTIC TACTICS FOR EARLY ANEMIA OF PREMATURE INFANTS WITH VERY LOW OR EXTREMELY LOW BIRTH WEIGHT: RETROSPECTIVE STUDY RESULTS - O. A. Senkevich; E. A. Smetanina; A. N. Yilg (Педиатрическая фармакология, 2016)
Background: Early anemia of prematurity (EAP) is a serious issue of contemporary neonatology due to increasing survivability of premature infants. One of the most efficient preventive methods is extreme prematurity prevention. At the same time, efficacy of different methods of EAP therapy remains undetermined.Objective: Our aim was to compare efficacy of erythrocyte-containing donor blood components (packed red cells, erythrocytic suspension) and recombinant epoetin beta for treating premature infants with EAP.Methods: The retrospective cohort study provided analysis of data of premature infants (gestation age — 27–32 weeks) born with very low (VLBW) and extremely low birth weight (ELBW) and EAP (hemoglobin < 110 g/l, hematocrit < 27%, reticulocyte share < 20‰, normochromia, normocytosis; all criteria must have been met). We determined primary hematological morphological parameters and population structure of umbilical (at birth) and peripheral blood (after 30 days of treatment) leukocytes.Results: 32 premature infants with EAP underwent donor blood component transfusions, 26 — recombinant epoetin beta injections. The groups were comparable in terms of the primary clinical laboratory parameters. In the donor blood component group, we observed lower hemoglobin concentration (108 ± 17 vs. 119 ± 16 g/l in the epoetin beta group; p = 0.07) and reticulocyte share (3.7 ± 1.5 vs. 8.7 ± 1.7‰, respectively; p = 0,053) at the age of 1 month. We revealed a drop in cell immunity parameters in the setting of donor blood component transfusions: CD4+ lymphocyte share — down to 32,2 ± 14,0% (in the epoetin beta group; p = 0.055); CD8+ lymphocyte share — down to 21,2 ± 7,1% (in the epoetin beta group; p = 0.050).Conclusion: Epoetin beta is more efficient in terms of EAP correction in premature infants with VLBW and ELBW that erythrocyte-containing donor blood component transfusions. The latter are characterized by adverse effect on cell immunity parameters.